Color Alteration of Encapsulated Beetroot (Beta vulgaris L.) Extract Upon Dissolving in Various pH Treatment - Lukitasari, Diah Mustika; Indrawati, Renny; Chandra, Rosita Dwi; Heriyanto, Heriyanto; Limantara, Leenawaty (Ma Chung Research Center for Photosynthetic Pigments, 2020)
It has been known that most natural pigments are unstable upon exposure against several environmental factors, such as thermal treatment, light, oxidizing or reducing agents, as well as acid or alkaline compounds. Encapsulation procedures is often adopted to adjust the solubility and provide protection to the natural pigments. Here, we prepared an encapsulated beetroot extract as the candidate of red bio-colorant. The primary aim of the present study is to investigate color alteration of encapsulated beetroot (Beta vulgaris L.) extract upon dissolving in various pH adjustment and prolonged storage. The McIllvainne buffer was prepared in various pH range, i.e. from 2 to 11. The encapsulated extract (0.1% w/v) was dissolved and the color of the solutions were measured regularly until 3 days storage under darkness at 200C. Any degradation or structural changes will cause color alteration, which were monitored through L*, a*, b* values, the hue angle (HÂ°), chroma values (C), as well as color difference (DE). The results showed that pH 4 was the most favorable condition that brings least impact to the color alteration, even when the colored solution was kept in prolonged storage until 9 days.